Anterior knee pain (patellar tendonitis) management and modification in bike fitting for track cyclist - Joseph, S.; Johar, M. S. N. M.; Ganason, R. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
An elite track cyclist experienced anterior knee pain in both knees over a 6 month period while training on his new bike and was diagnosed with patellar tendonitis. A bike fitting session was conducted followed by sprint performance on a trainer. When sprinting the cyclist slipped (7 cm ±1.7) forward from the initial position on the saddle leading to his knee joint shifting ahead of the pedal at 11 o`clock position and resulted in irritation and pain on the patellar tendon. An intervention was done to increase the handlebar height and to change the stem bar. It was then observed that the tendency to slip forward at sprints immensely decreased. The cyclist was then asked to familiarize themselves with the new bike setting for a period of 3 weeks and provide feedback where he reported that the pain had considerably reduced and he could regain his previous performance.